An architecture for wireless networks with SINR constraints and its performance upperbounds - Kucera, S.; Zhang Bing (2009 International Conference on Networking and Media Convergence, 2009)
This paper introduces a novel architecture for mobile communication networks with guaranteed quality of service. For comparison purposes, performance upperbounds of the whole system are derived subsequently. Their numerical evaluation in real-life simulation scenarios shows that our proposal significantly outperforms the state-of-the-art IEEE 802.11 technology in random topologies with varying traffic and mobility. Importantly, the complexity of the proposed scheme is comparable to the one of the IEEE standards, thus enabling implementation by means of low-cost hardware. The proposed architecture consists of three cross-layer optimized layers, which optimally manage energy and frequency spectrum resources of the network using a purely distributed, asynchronous, and non-cooperative approach.